Halal Industry in Indonesia; Challenges and Opportunities - Ferry Khusnul Mubarok; Muhammad Khoirul Imam (Journal of Digital Marketing and Halal Industry, 2020)
The global halal industry has shown significant development, and Indonesia has become one of the countries with great potential. This study aims to identify opportunities and challenges in developing the halal industry in Indonesia. This research uses a qualitative approach. Data sources used in the form of secondary data, which comes from library sources—technical analysis of data using the SWOT analysis approach. The results showed that the development of the halal industry in Indonesia included several sectors, namely the food and beverage sector, tourism, fashion, media and recreation, pharmaceuticals and cosmetics, and renewable energy. Based on SWOT analysis, it was found that there are strengths, weaknesses, opportunities, and challenges in developing the halal industry in Indonesia. Thus, in the future, to improve the halal industry in Indonesia, it is necessary to optimize the synergy of various elements ranging from the community, industry players, government, financial institutions, associations, academics, and educational institutions, as well as other related parties.